An Integrated Pest Management System Development: An Economic Valuation Analysis - Syarif, Nur Yulia; Waridin, Waridin (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to determine the socio-economic characteristics of Tajuk Village farmers and determine the conditions as well as management of agriculture on broccoli and cabbage vegetables, also designing alternative proposals for management of conventional farming systems into agriculture using an Integrated Pest Management system in Tajuk Village, Semarang District. By using Mix Method, a combination of qualitative and quantitative approaches, the research was to determine the amount of farmers’ willingness to pay using the Contingent Valuation Method and see the benefits that could be obtained with a different farming system. The results showed that by using the Willingness to Pay (WTP) Analysis, there were 94.55% of farmers in Tajuk Village who were willing to pay the value of the offer given. Thus, it obtained an average value of WTP of IDR 41,000 with a total value of WTP on changes in the Integrated Pest Management system of IDR 3,034,000 per harvest. Besides, the total annual WTP value was IDR 6,068,000. This WTP value can be used as the cost of planning the development of an Integrated Pest Management system in Tajuk Village by collaborating with the development plan by the Stakeholders in the planned program involvement. The stakeholders classified as key players were the Agriculture and Plantation Office, Horticultural Food Crops Research Institute (BPTPH), Pest Disease Control (PHP), Plant Disturbing Organism Observers (POPT), and Head of Farmer Groups. The actors were the Village Authority, Sub-district Authority, and business people. While academics act as context setters.